First Flight from Europe to the South Atlantic - Silva, André (2022)
The History of the transatlantic flights goes back to 1919 and began with a flight performed from Newfoundland to Lisbon; two weeks later another flight was performed between Newfoundland and Ireland. On 1922, the Portuguese airmen Gago Coutinho and Sacadura Cabral crossed the South Atlantic Ocean by air in a flight performed exclusively with internal means of navigation: a new instrument that consisted in a type of sextant improved with two spirit levels to provide an artificial horizon and also with the help of a “path corrector”. Despite this journey had lasted 79 days to cross South Atlantic Ocean, their flight time was only 62:26 minutes, and they’ve flown 8,383 nautical miles, using 3 different hydroplanes christened: Lusitania, Pátria and Santa Cruz. Despite this journey had lasted 79 days, their flight time was only 62 h 26 m; they’ve flown 8,383 nautical miles using 3 different hydroplanes christened: Lusitania, Pátria and Santa Cruz. The new artificial horizon sextant had proven itself while flying over the ocean, without external references.